Perspektif Psikologi dalam Merespons Perubahan Peran Kerja akibat AI - Pratama, Dika Agus; Faadhil, Faadhil (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
The development of artificial intelligence (AI) has drastically transformed the landscape of work, creating uncertainty and psychological pressure for many workers. This article aims to examine how psychological perspectives, particularly positive and organizational psychology, can be employed to respond to AI-driven changes in work roles. This study uses a qualitative literature review approach, drawing on scholarly articles and policy reports from various disciplines and global contexts. Findings indicate that while AI induces anxiety and stress due to new job demands, it also presents opportunities for adaptation if supported by strengthened psychological capital such as optimism and resilience. Additionally, soft skills such as empathy and emotional intelligence remain essential competencies that AI cannot replace. Organizational psychology and public policy play a strategic role in fostering fair and supportive work ecosystems through psychological assessment-based interventions and human-centered work design. This review underscores the importance of integrating psychological approaches in navigating workforce transformations in the digital age.